2019
DOI: 10.1038/s41436-018-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel computerized decision aid for aneuploidy screening: a randomized controlled trial

Abstract: Knowledge surrounding aneuploidy screening in women who used a DA was not inferior to knowledge in women who underwent GC. Use of the DA in addition to GC reduced decisional conflict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…This indicated that women using decision support tools felt more informed and were more aware of the risk and expected outcome of each option when compared to their counterparts [ 19 - 21 , 23 , 27 ]. Women using decision support tools also had better knowledge scores [ 19 , 21 - 23 , 25 - 27 ], except for in 2 studies [ 20 , 24 ] which showed no effect on knowledge. Both digital and paper-based decision support tools showed no difference in attitudes and frequency of completing screening (digital: 32%; paper-based: 15%; P= .087) [ 19 , 23 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that women using decision support tools felt more informed and were more aware of the risk and expected outcome of each option when compared to their counterparts [ 19 - 21 , 23 , 27 ]. Women using decision support tools also had better knowledge scores [ 19 , 21 - 23 , 25 - 27 ], except for in 2 studies [ 20 , 24 ] which showed no effect on knowledge. Both digital and paper-based decision support tools showed no difference in attitudes and frequency of completing screening (digital: 32%; paper-based: 15%; P= .087) [ 19 , 23 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, whether gained knowledge lasted over time is unknown. One study [ 20 ] found no difference in knowledge between women receiving genetic counseling about prenatal screening with and without a supplementary app. The fact that both groups received a high-standard intervention such as genetic counseling could possibly explain why there was no additional benefit of the app on knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…While it is important to improve pregnant women’s access to prenatal GC, it is paramount that their reported outcomes be considered when implementing alternative GC SDMs. Previous studies have demonstrated the utility of providing digital information on prenatal testing before in-person GC, which was confirmed to help improve patients’ knowledge [ 13 , 21 ], shorten the time required [ 21 ], and reduce decision conflict [ 13 , 16 , 20 ]. Considering our finding that Japanese women tend to prefer in-person GC, such an approach would likely be acceptable in a Japanese population.…”
Section: Discussionmentioning
confidence: 97%
“…The decisional con ict of women in deciding to terminate the pregnancy was reduced after counseling on all sub scales of awareness, transparency of values, con dence, support, and effective decision, and it was decided to terminate the pregnancy with less con ict [24]. Carlson et al (2019) also studied the effect of computer-aided decisionmaking on decisional con ict on aneuploidy screening. This showed that the decisional con ict in the intervention group decreased after receiving the computer aided decision-making to perform aneuploidy screening (p < 0.003) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Carlson et al (2019) also studied the effect of computer-aided decisionmaking on decisional con ict on aneuploidy screening. This showed that the decisional con ict in the intervention group decreased after receiving the computer aided decision-making to perform aneuploidy screening (p < 0.003) [27]. The decision aid methods such as education, and counseling while raising awareness can help people to understand better their personal values, and participate in the decisions and make better decisions with more certainty based on the available evidence and options with the support of health care providers and families without being forced to make decisions.…”
Section: Discussionmentioning
confidence: 99%